2021
DOI: 10.2196/24214
|View full text |Cite
|
Sign up to set email alerts
|

Supervised Exercise Therapy Using Mobile Health Technology in Patients With Peripheral Arterial Disease: Pilot Randomized Controlled Trial

Abstract: Background Mobile health interventions are intended to support complex health care needs in chronic diseases digitally, but they are mainly targeted at general health improvement and neglect disease-specific requirements. Therefore, we designed TrackPAD, a smartphone app to support supervised exercise training in patients with peripheral arterial disease. Objective This pilot study aimed to evaluate changes in the 6-minute walking distance (meters) as a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…There were different tools used to measure physical activity for these studies. One study used the 6-minute walk test, [ 13 ] an abridged 12-item version of the Intrinsic Motivation Inventory [ 12 ], and daily step count [ 10 ]. For instance, Martin et al [ 10 ] observed that the population that received text message reminders walked close to 2534 daily steps more than those who did not get the text messages reminders (95% CI: 1318–3750; p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were different tools used to measure physical activity for these studies. One study used the 6-minute walk test, [ 13 ] an abridged 12-item version of the Intrinsic Motivation Inventory [ 12 ], and daily step count [ 10 ]. For instance, Martin et al [ 10 ] observed that the population that received text message reminders walked close to 2534 daily steps more than those who did not get the text messages reminders (95% CI: 1318–3750; p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…The studies were studies published between 2011 and 2021. Two of the studies were conducted in the U.S.A [ 10 , 11 ] and two in Finland [ 12 , 13 ], and the rest we conducted per region including India [ 14 ], Belgium [ 15 ], China [ 16 ], Spain [ 17 ], China and India [ 18 ] combined, and finally the Kaiser Permanente health plan regions (Northwest, Hawaii, and Georgia) [ 19 ]. The longest study duration was 12 months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing interest to use telemedicine as an innovative tool to enhance both supervised and home-based exercise programs, with the development of wearable activity monitors and applications to enhance education and patients’ adherence [ 57 , 58 , 59 , 60 , 61 ]. Several reviews and systematic analyses provided an overview of randomized controlled clinical trials that aimed at investigating the efficiency of telemedicine-enhanced exercise programs on patients’ outcomes [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ] ( Table 1 ).…”
Section: Telemedicine and Lower Extremity Artery Diseasementioning
confidence: 99%
“…Telemedicine applications used varied and included telemonitoring with wearable sensors and physical activity trackers [ 62 , 63 , 64 , 67 , 68 ], as well as telecoaching applications using smart technology (computers or mobile phones) [ 65 , 66 , 69 , 73 ]. The clinical trials included symptomatic patients with intermittent claudication; one study also involved patients who had previously received peripheral endovascular therapy [ 65 ] and one involved asymptomatic patients with LEAD [ 68 ].…”
Section: Telemedicine and Lower Extremity Artery Diseasementioning
confidence: 99%